Insights into the single and binary adsorption of copper(II) and nickel(II) on hexagonal boron nitride: Performance and mechanistic studies - Oh, W.-D. (2019)
A series of hexagonal boron nitrides (h-BNs) was developed using a facile method involving pyrolysis of urea and boric acid mixture at different temperatures. The as-prepared h-BNs were characterized using XRD, FESEM, FTIR, BET and XPS and the results indicated that the as-prepared h-BNs consist of microparticle structures with BET specific surface area between 12-18 m 2 g -1 . The h-BN prepared at 750Â°C (BN-750) displayed excellent adsorption capacities for both Cu(II) and Ni(II) (up to 200 and 95 mg g -1 , respectively) compared to those prepared at other temperatures. At higher metal ion concentrations (>250 mg L -1 ), multilayer adsorption was observed. The equilibrium adsorption modelling study indicated that the adsorption process was best fitted to the Langmuir (R 2 >0.97) and Sips (R 2 >0.98) isotherm models. The binary adsorption of Cu(II) and Ni(II) was also investigated and the results revealed that the BN-750 has higher adsorption affinity for Cu(II) compared to Ni(II). Detailed analyses of the spent adsorbent using XPS and FTIR indicated that the oxygen functional groups of BN-750 played an important role in facilitating the electrostatic attraction and complexation of heavy metal during adsorption process. Furthermore, the results confirmed that Cu(II) and Ni(II) occupied the same active sites on BN-750. The results of this study revealed insights into the adsorption mechanism of Cu(II) and Ni(II) on BN-750 and demonstrated that the as-prepared h-BN is a promising adsorbent for efficient heavy metal removal in aqueous system. Â© 2019 Elsevier Ltd. All rights reserved.